The Correlation Between Language Learning Beliefs and English Academic Achievement - Nonoy, Intan; Neman, Meily Ivane Esther (Jurnal Educatio FKIP UNMA, 2025)
The purpose of this study was to find out the relationship between Students’ language learning beliefs and English academic achievement in SMP Advent UNKLAB. This study also aimed to find the level of Students’ language learning beliefs and English academic achievement. The researcher adapted the questionnaire from E. Horwitz (1988) that was distributed to grade VIII parallel A, B, C, and D with a total number of 115 students at SMP Advent UNKLAB, which is located in Airmadidi North Sulawesi who were enrolled in the first semester of the academic year 2024/2025. Descriptive analysis of mean score and Pearson Product Coefficient Correlation were used to answer the research questions. The results showed that: (1) the level of Students’ language learning beliefs was 4.46 indicating a high level, (2) the level of English academic achievement was 78.52, indicating a good level and (3) r = 0.004 and p = 0.966 showing there is no significant correlation between Students’ language learning beliefs and English academic achievement.